How community interactions contribute to harmonious community relationships and customers' identification in online brand community. Issue 5 (October 2016) - Luo, Nuan; Zhang, Mingli; Hu, Mu; Wang, Yu
Highlights: Community interactions are positively associated with harmonious community relationships. Harmonious community relationships enhance community identification. Community interaction characteristics have positive interactive effect on community relationships. Abstract: As a proxy for the vitality of online brand community, effective interaction has always been viewed as a prerequisite for the formation of harmonious organization atmosphere and high degree of organizational identity. To investigate the process, this study proposes a model delineates the relationship among community interactions, harmonious community relationships, and customers' community identification. The findings, based on 665 valid samples, reveal that different community interactions (product-information, human-computer, and interpersonal) have different effects on harmonious community relationships (customer-brand and customer-other customers' relationships), which in turn influences customers' identification with community. Furthermore, these community interactions have an interactive effect on harmonious community relationships. Based on the analytical results, this study concludes with some managerial and research implications.